Schaum's outline of basic circuit analysis - O'Malley, John R. 4 0 16; 5 (New York : McGraw-Hill, 2011)
Provide seven hundred fully solved problems in a review of basic circuit analysis.
Basic concepts -- Resistance -- Series and parallel DC circuits -- DC circuit analysis -- DC equivalent circuits, network theorems, and bridge circuits -- Operational-amplifier circuits -- PSpice DC circuit analysis -- Capacitors and capacitance -- Inductors, inductance, and PSpice transient analysis -- Sinusoidal alternating voltage and current -- Complex algebra and phasors -- Basic AC circuit analysis, impedance, and admittance -- Mesh, loop, nodal, and PSpice analyses of AC circuits -- AC equivalent circuits, network theorems, and bridge circuits -- Power in AC circuits -- Transformers -- Three-phase circuits.
Includes index.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Electric circuit analysis;Electric circuit analysis -- 20 -- Problems, exercises, etc.;Outlines, syllabi, etc; 20; 2